Solitary wave-series solutions to non-linear Schrodinger equations - Azram, Mohammad; Zaman, Haider (IIUM Press, 2012)

(untitled)
In this paper, higher-order dispersive nonlinear Schrodinger equations are studied. Their solitary wave-series solutions with continuity of derivatives and discontinuity of derivatives at crest are presented. Convergence of the series solutions is also properly checked and discussed with the help of graphs.